Sosialisasi dan Edukasi Lingkungan Hidup di SMA Islam An Naas Pekanbaru - Insusanty, Enny; Ikhwan, M; Lestari, Ika (FLEKSIBEL: Jurnal Pengabdian Masyarakat, 2022)
The school yard is one of the public areas that can be used for various educational activities for students. Increasing the understanding of An Naas Islamic High School students regarding the environment, socialization and education were carried out through the delivery of material directly in the form of lectures and counseling to high school students, then training on sorting waste and planting trees around the school yard was carried out. Community service activities with partner students of SMA Islam An Naas have been carried out well and successfully. This is shown by the increasing knowledge of partners in socialization and environmental education to 94% by planting and caring so that trees grow well. Partners have maintained cleanliness by disposing of waste by sorting the waste first. Keywords: Environment, socialization, education, garbage, reforestation